2017
DOI: 10.1021/acs.inorgchem.7b01131
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformation in Inverse-Perovskite REPt3B (RE = Sm and Gd–Tm) Associated with Large Volume Reduction

Abstract: In this work, we report the structural phase transformation of tetragonal inverse-perovskite REPtB (RE = Sm, and Gd-Tm) compounds to cubic perovskite structure, with a large volume reduction of about 9% (reduction of the c axis, ∼17%; increase in the a axis, ∼5%). The structural stability of the cubic phase, however, could only be maintained by lowering the lattice parameter of the off-stoichiometric REPtB (x < 1), formed in the process of annealing. The combined effect of phase transformation and stoichiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…The RIr 3 system thus form as a macroscopic coexistence of two crystalline phases, cubic C15b and cubic AuCu 3 -type with different relative percentage for different rare earths (Table I). Coexistence of similar polymorphic phases have earlier been reported in literature 11,22 . For example it is recently reported that RPt 3 B compounds form in two polymorphic crystal structures, tetragonal CePt 3 B-type and and ideal cubic perovskite-type at room temperature 11 .…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The RIr 3 system thus form as a macroscopic coexistence of two crystalline phases, cubic C15b and cubic AuCu 3 -type with different relative percentage for different rare earths (Table I). Coexistence of similar polymorphic phases have earlier been reported in literature 11,22 . For example it is recently reported that RPt 3 B compounds form in two polymorphic crystal structures, tetragonal CePt 3 B-type and and ideal cubic perovskite-type at room temperature 11 .…”
Section: Resultssupporting
confidence: 83%
“…To check the homogeneity of the materials, EDX measurement have been carried out which confirms that the RIr 3 compounds are chemically homogeneous with rare earth and transition metal ratio 1:3. It therefore appears to be quite likely that these compounds form in new crystal structure or the extra peaks may come from coexisting additional polymorphic phase similar to that reported earlier in RPt 3 B series of compounds 11 . It may also be pointed out here that binary TbPt 3 compounds are also known to form in two different polymorphic phases TbPt 3 : C15b and AuCu 3 -type 12 .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Recently, they are emerging as potential applicants for topological insulators and three‐dimensional Dirac electron systems . A series of rare‐earth–based inverse perovskites have been studied for various properties to find vital application in various fields . Several inverse perovskites have been prepared, characterized, and studied like A 3 NIn, A 3 NSn, and A 3 XAl, where (A = Sc, La, Ce, Pr, Nd, Sm, Gd‐Tm, Lu) and (X = C, N, O).…”
Section: Introductionmentioning
confidence: 99%
“…17 A series of rare-earth-based inverse perovskites have been studied for various properties to find vital application in various fields. [18][19][20][21][22][23] Several inverse perovskites have been prepared, characterized, and studied 24,25 like A 3 NIn, A 3 NSn, and A 3 XAl, where (A = Sc, La, Ce, Pr, Nd, Sm, Gd-Tm, Lu) and (X = C, N, O). The electronic and magnetism properties of Gd 3 AlX (X = B, N) were investigated by Kacimi et al 26 We have further extended the investigation on these materials for elastic, thermodynamic, thermoelectric, and optical properties for various applications.…”
Section: Introductionmentioning
confidence: 99%